The Influence of Hydration Education on Kidney Health Behavior in Elementary School Children in Magelang City - Lulut Handayani (Poltekkes Kemenkes Semarang, 2026)
Background: The capability of the kidneys to control the volume and concentration of urine is essential for sustaining water equilibrium, independent of fluid consumption. Renal ailments, such as renal failure, are becoming more prevalent among children, with some requiring hemodialysis early in life due to significant kidney impairment. Extensive observational research indicates that sufficient hydration may have a beneficial effect in the prevention of chronic kidney disease, signaling the necessity for initiatives aimed at enhancing awareness regarding proper fluid consumption. Purpose: This aims of this study to determine the effect of hydration education on hydration habits as a component of kidney health behavior among elementary school children in Magelang City. Methods: This study employed a ore-experimental design with a one-group, pretest and post-test only approach. The research subjects consisted of 29 elementary school children. Data collection was carried out by screening the respondents' kidney health, specifically their drinking habits. Following the screening, the respondents received education on hydration and kidney health. After the education, their kidney health behaviour was assessed. Results: Based on the Wilcoxon test analysis, the results showed a p-value of 0.000, meaning p < 0.05. Conclusion: This indicates that there is a significant effect of hydration education on kidney health behaviour in elementary school children.